(untitled) (Journal of Guidance and Counselling Studies, 2023)
The epidemic of crises in various forms ravaging our dear nation Nigeria has plunged a good number of her citizens into a life of fear. Most people feel threatened by one thing or the other and so live with the fear of being harmed everyday of their lives. This opinion paper X-ray the reality of fear in our contemporary society against the counselling responsibility of the Counsellor. Some useful counselling techniques were identified with which counsellors could support people to manage their fears. ThePaper recommends The CBT as a helpful tool for the Counsellor.